Local Mucosal CO2 but Not O2 Insufflation Improves Gastric and Oral Microcirculatory Oxygenation in a Canine Model of Mild Hemorrhagic Shock - Hof, Stefan; Truse, Richard; Weber, Lea; Herminghaus, Anna; Schulz, Jan; Weber, Andreas P. M.; Maleckova, Eva; Bauer, Inge; Picker, Olaf; Vollmer, Christian (Frontiers in Medicine, 2022)
Acute hemorrhage results in perfusion deficit and regional hypoxia. Since failure of intestinal integrity seem to be the linking element between hemorrhage, delayed multi organ failure and mortality, it is crucial to maintain intestinal microcirculation in acute hemorrhage. During critical bleeding physicians increase FiO2 to raise total blood oxygen content. Likewise, a systemic hypercapnia was reported to maintain microvascular oxygenation (µHbO2). Both, O2 and CO2, may have adverse effects when applied systemically that might be prevented by local application. Therefore, we investigated the effects of local hyperoxia and hypercapnia on the gastric and oral microcirculation. Methods: Six female foxhounds were anaesthetized, randomized into eight groups and tested in a cross-over design. The dogs received a local CO2-, O2- or N2-administration to their oral and gastric mucosa. Hemorrhagic shock was induced through a withdrawal of 20% of estimated blood volume followed by retransfusion 60 min later. In control groups no shock was induced. Reflectance spectrophotometry and laser Doppler were performed at the gastric and oral surface. Oral microcirculation was visualized by incident dark field imaging. Systemic hemodynamic parameters were recorded continuously. Statistics were performed using a two-way-ANOVA for repeated measurements and post-hoc analysis was conducted by Bonferroni testing (p < 0.05). Results: The gastric µHbO2 decreased from 76 ± 3% to 38 ± 4% during hemorrhage in normocapnic animals. Local hypercapnia ameliorated the decrease of µHbO2 from 78 ± 4% to 51 ± 8%. Similarly, the oral µHbO2 decreased from 81 ± 1% to 36 ± 4% under hemorrhagic conditions and was diminished by local hypercapnia (54 ± 4%). The oral microvascular flow quality but not the total microvascular blood flow was significantly improved by local hypercapnia. Local O2-application failed to change microvascular oxygenation, perfusion or flow quality. Neither CO2 nor O2 changed microcirculatory parameters and macrocirculatory hemodynamics under physiological conditions. Discussion: Local hypercapnia improved microvascular oxygenation and was associated with a continuous blood flow in hypercapnic individuals undergoing hemorrhagic shock. Local O2 application did not change microvascular oxygenation, perfusion and blood flow profiles in hemorrhage. Local gas application and change of microcirculation has no side effects on macrocirculatory parameters.